2014
DOI: 10.1016/j.asr.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

The KASCADE-Grande energy spectrum of cosmic rays and the role of hadronic interaction models

Abstract: Previous results obtained by KASCADE-Grande using the QGSjetII-02 hadronic interaction model have shown that the energy spectrum of cosmic rays between 10 16 eV and 10 18 eV exhibits a significant hardening at approximately 2 Â 10 16 eV and a slight but statistically significant steepening close to 10 17 eV. Moreover, the analysis with QGSjetII-02 suggests that the break observed around 10 17 eV is caused by the heavy component of primary cosmic rays. In this paper, we report on the results of similar analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…An indication of a hardening of the light component just above 10 17 eV has been measured as well [31]. The flux of heavy and light components depends on the hadronic interaction model used to interpret the experimental data [32] as previously mentioned. The above results are summarised on Fig.…”
Section: The Knee Region Up To the Anklementioning
confidence: 99%
“…An indication of a hardening of the light component just above 10 17 eV has been measured as well [31]. The flux of heavy and light components depends on the hadronic interaction model used to interpret the experimental data [32] as previously mentioned. The above results are summarised on Fig.…”
Section: The Knee Region Up To the Anklementioning
confidence: 99%
“…The details of these findings rely on the results of simulations and the description of hadronic interactions for reconstructing the properties of the primary particle which differ in predictions. However, a cross-check of the results obtained with various pre-LHC interaction models showed that, qualitatively, similar features are present in the spectra, independently of the interaction model used to interpret the data [4,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Such results are compared to those obtained using the pre-LHC versions of these models, EPOS 1.99 and QGSjetII-02, as well as those obtained using SIBYLL 2.1 [10] hadronic interaction model (see [4,5,6] for details). Moreover, the analysis presented in this paper is based on the full statistics accumulated by KASCADE-Grande during its operational time between 2002 and 2013.…”
Section: Introductionmentioning
confidence: 99%
“…The selection of heavy primaries enhances the knee-like feature that is already present in the all-particle spectrum. The analysis was repeated on the basis of different hadronic interaction models [18,19]. Despite the fact that the relative abundance of the heavy particles varies significantly dependent on the model in use, the spectral feature of this 'heavy' knee is visible in all the spectra.…”
Section: Elemental Composition Of Cosmic Raysmentioning
confidence: 99%